Solving Tomorrow’s Problems Today? Daily Anticipatory Coping and Reactivity to Daily Stressors - Neupert, Shevaun D. (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES: The present study examined the day-to-day fluctuation of state-like anticipatory coping (coping employed prior to stressors) and how these coping processes relate to important outcomes for older adults (i.e., physical health, affect, memory failures). METHOD: Forty-three older adults aged 60–96 ( M = 74.65, SD = 8.19) participated in an 8-day daily diary study of anticipatory coping, stressors, health, affect, and memory failures. Participants reported anticipatory coping behaviors on one day with respect to 6 distinct stressor domains that could occur the following day. RESULTS: Multilevel models indicated that anticipatory coping changes from day to day and within stressor domains. Lagged associations suggested that yesterday’s anticipatory coping for potential upcoming arguments is related to today’s physical health and affect. Increased stagnant deliberation is associated with reduced cognitive reactivity (i.e., fewer memory failures) to arguments the next day. DISCUSSION: Taken together, these findings suggest that anticipatory coping is dynamic and associated with important daily outcomes.